Nudging social online referrals: Evidence from a randomized field experiment - ZENG, Qian (Institutional Knowledge at Singapore Management University, 2022)
With the rise of social commerce platforms and customer engagement in online products and services, firms are focusing their attention on effective social online referral program to encourage customers’ online referral behaviors to grow their customer base. Hence, how to influence customers to participate in online referral is a matter of the utmost importance to firms. However, little empirical research has examined the impact of online referral program on customers’ online referral on social commerce platform. To close this research gap, this dissertation investigates the effectiveness of digital nudging for consumers’ social online referral on social commerce platforms. Working with a leading home appliances and consumer electronics company, we conducted a large-scale randomized online field experiment of digital nudging on a social commerce platform. Drawing upon the nudging theory and Persuasion Principle, this research uses a field experiment with 4,200 participants to examine the role of nudging persuasive framed messages using product scarcity and social proof heuristics in influencing consumers’ social online referral. The results of the experiment suggest that both persuasive framed messages with product scarcity and social proof heuristics positively impact customers’ online referrals, comparing to the control group without nudging persuasive framed message. In terms of persuasive framed message, using low-level scarcity heuristic is more effective than social proof heuristic on online referral, while high-level scarcity heuristics is less effective than low-level scarcity heuristics. A higher level of scarcity might signal that an item has been taken by many people and its “status symbol” decreases, which dilutes the exclusivity and uniqueness of the item. This research contributes to the literature on digital nudging and Persuasion Principle by providing evidence of the types of persuasion heuristics that are effective in influencing customers’ online referral on social media platform.